Advancing head and neck cancer following the coronavirus disease 2019 pandemic. Issue 11 (21st November 2022) - Flynn, W; Maqsood, R; Maseland, T; Montgomery, J; Douglas, C
Abstract: Objective: Delay in the diagnosis of head and neck cancer can result in significant excess morbidity and mortality. How the pandemic has affected patient presentation in Scotland is unknown. Method: This retrospective cohort study compared all presentations of head and neck cancer between June and October of 2019 with the same period following the peak of the pandemic in 2020 in West Scotland, a region populated by 2.5 million people. Results: A total of 528 patients met our inclusion criteria. Compared with 2019, patients in 2020 were more likely to present with a higher American Joint Committee on Cancer stage (odds ratio, 1.67 (95 per cent confidence interval = 1.20 to 2.31); p = 0.002), a longer preceding symptom duration (odds ratio, 2.03 (95 per cent confidence interval = 1.44 to 2.87; p < 0.001) and to have an emergency presentation (odds ratio, 2.53, (95 per cent confidence interval = 1.15 to 5.55; p = 0.017). Conclusion: Patients are presenting later with more advanced head and neck cancer following the coronavirus disease 2019 pandemic.